Tentang Cara Pandang Sekuler dan Rohani - Dwi Maria Handayani (Reformed Center for Religion and Society, 2023)
Christianity is only a religion if the dichotomy of secular and spiritual thoughts is the base of it. It has nothing to do with the objective truth we believe. Christianity is only a chosen belief or simply a desire to fulfil an inner desire. However, this is very difficult or even impossible in practice. How can a person make such a sharp division between the spiritual and the secular within himself? How can someone's actions and thoughts separate from his religion or belief in the public sphere?